2022
DOI: 10.1108/pr-05-2021-0343
|View full text |Cite
|
Sign up to set email alerts
|

Can HRM predict mental health crises? Using HR analytics to unpack the link between employment and suicidal thoughts and behaviors

Abstract: PurposeThe aim of this research is to determine the extent to which the human resource (HR) function can screen and potentially predict suicidal employees and offer preventative mental health assistance.Design/methodology/approachDrawing from the 2019 National Survey of Drug Use and Health (N = 56,136), this paper employs multivariate binary logistic regression to model the work-related predictors of suicidal ideation, planning and attempts.FindingsThe results indicate that known periods of joblessness, the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 94 publications
1
12
0
Order By: Relevance
“…HR analytics is a powerful tool to predict employee at in various stages of their careers (Khan and Tang, 2017). The pandemic period witnessed increasing support of HR analytics towards mental health support, as the pandemic raised issues related to employment uncertainty and negative thoughts (Hastuti and Timming, 2023;Cooke and Xu, 2023). Moreover, supportive technologies that do not elicit concerns related to identity threat and stigma associated with mental health concerns, also ensure a comfortable environment for the employees (Brouwers et al, 2020;Xing et al, 2021).…”
Section: Hr Analytics and Organisational Mental Health Supportmentioning
confidence: 99%
See 2 more Smart Citations
“…HR analytics is a powerful tool to predict employee at in various stages of their careers (Khan and Tang, 2017). The pandemic period witnessed increasing support of HR analytics towards mental health support, as the pandemic raised issues related to employment uncertainty and negative thoughts (Hastuti and Timming, 2023;Cooke and Xu, 2023). Moreover, supportive technologies that do not elicit concerns related to identity threat and stigma associated with mental health concerns, also ensure a comfortable environment for the employees (Brouwers et al, 2020;Xing et al, 2021).…”
Section: Hr Analytics and Organisational Mental Health Supportmentioning
confidence: 99%
“…The use of technological and analytical support for addressing mental health concerns gained significant acceptance during the pandemic (Figueroa and Aguilera, 2020). Organisations also started relying on analytics to predict and find solutions for mental health issues (Hastuti and Timming, 2023). Studies have shown that technology facilities in the mental health domain effectively support the mental well-being of users (Anttila et al, 2021;Grov e, 2021).…”
Section: Hr Analytics and Mental Well-beingmentioning
confidence: 99%
See 1 more Smart Citation
“…This trend is seen in the human resources (HR) field and has given rise to the emergence of people analytics , a field that leverages data to generate valuable insights, enabling better decision-making, enhancing the employee experience, and improving overall organizational performance (Brock, 2017; Gal et al, 2020; Hastuti & Timming, in press; McCartney & Fu, 2022). Reflecting this trend, academic output on people analytics has increased rapidly, with human resource management (HRM) journals such as HRM and Journal of Organizational Effectiveness: People and Performance publishing special issues on various forms of people analytics, including workforce analytics and human capital analytics.…”
Section: Introductionmentioning
confidence: 99%
“…Current human resource (HR) interventions such as mental health training and Employee Assistance programs (EAP) are insufficient to solve these issues. Hence, there is a need for the HR function to take a proactive stance in helping organizations address this issue (Hastuti and Timming, 2023).…”
mentioning
confidence: 99%